The pathogenic organism in high vaginal swab among pregnant women at Hospital Tuanku Fauziah from March to May / Nor Farhanah Mohd Noor - Mohd Noor, Nor Farhanah (2017)
The aim of the study was to determine the pathogen organisms in high vaginal swab among pregnant women in Hospital Tuanku Fauziah from March to May 2017. Pathogen organism is the microorganism that can cause disease when invade human body. Not all the microorganism is pathogen in certain circumstances. It is depends on the clinical judgement whether it can cause harm to the body or not. Therefore, in this research, we only focus on the organism that can cause disease to pregnant women at Hospital Tuanku Fauziah. The organism that usually found in pregnant women are Streptococcus agalactiae (Strep B), Yeast, and Colliform. Women that pregnant are at risk of getting infected with these pathogen organisms. The study design was cross-sectional study, which was the data obtained from the hospital was chosen as the study design project. Collection of data for cases of pathogen organism in high vaginal swab among pregnant women were from June 2017 until July 2017. The number of HVS sample positive with pathogen organism among pregnant women was 210 which were more than pathogen organism in non-pregnant women (55). The most prevalence among the pathogen organism was yeast followed by Streptococcus Agalactiae and the most least was coliform. The number of pathogen organisms in high vaginal swab among pregnant women were decreasing in March, April, and May which were 82, 66,and 63 respectively. So we can conclude that there was significant of pathogenic organisms in high vaginal swab among pregnant women at HTF from March to May.